Preferensi Orang Tua di Keluarga Indonesia di Pulau Jawa dalam Mencari Informasi Mengenai Covid 19 - Yuli Nugraheni; Brigitta Revia Sandy Fista (LPPM Stikosa - AWS, 2022)
Research on the preferences of Indonesian families on the island of Java in seeking information regarding Covid 19 through social media was carried out with the aim of knowing the choice of media and the type of information sought by families on the island of Java regarding Covid 19. The study was focused on the island of Java because until now the distribution of daily cases The highest number of COVID-19 is in Java, namely in West Java, Central Java, East Java, DKI, DIY, and Banten. This research was conducted with a quantitative approach with descriptive research types and survey research methods conducted online with a sample of 100 families consisting of mothers and fathers. which are spread over 6 provinces in Java Island which will be taken using cluster sampling technique. The theory used is uses and gratification, preference, information seeking and social media. The results show that father's media exposure is a social network with the Instagram application. The most sought-after information is information about the spread of Covid cases in the world and Indonesia. The frequency of searching for information on covid is carried out every day with a duration of less than 2 hours. Mother's media exposure can be concluded as follows: social network with Facebook application. The most sought-after information is information about the spread of Covid cases in the world and Indonesia. The frequency for searching for information on covid is carried out every day with a duration of less than 2 hours. Keywords: preference; family; media; covid 19